Association of Body Mass Index with Orexin- A Levels in Reproductive Age Group Women - Munazza Khan, Zafaruddin, Shama Iqbal, Fareeha Hasan, Maryam Mastoor, (Pakistan Journal of Medical & Health Sciences, 2022)
Background and Aim: Orexin-A are hypothalamic neuropeptides contributing to regularization of neuroendocrine homeostasis, feeding behavior and sleep-wakefulness rhythm. Blood pressure, sympathetic activation, blood glucose level, and metabolic status is controlled by neuropeptide. The present study aimed to evaluate the association of body mass index with Orexin-A levels in reproductive age group women. Methodology: This cross-sectional study was carried out on 120 healthy reproductive age group women at the Department of Physiology, Lady Reading Hospital, Peshawar from November 2020 to April 2021. Prior to study conduction, ethical approval was taken from the institute ethical committee. Informed written consent was obtained from each individual. All the healthy women of reproductive age group with age range from 18 years to 40 years were enrolled. Women with obstetrical problems and had pregnancy were excluded from the study. A pro-designed proforma was used for taking medical history and complications of each participant. All the participants underwent standardized questionnaire based interview regarding medical history, menstrual history, and obstetrical history. Anthropometric parameters of each participant was measured. Orexin-A/hypocretin-enzyme immunoassay kit was utilized for the measurement of fasting serum orexin levels. For data analysis and descriptive statistics, SPSS version 25 was used. Results: Of the total 120 reproductive age group women, about 66 (53%) were in age group 18 to 25 years followed by 25 (20.8%) between 26 and 30 years, 17 (14.2%) in 31 to 35 years, and 12 (10%) in 35 to 40 years. Based on different age group women, the mean serum orexin-A levels ranged from 47.26±16.48 pgm/ml for women aged above 35 years to 51.31±13.89 pgm/ml for 26 to 30 years. However, no significant association were revealed in both group with statistically significant of P=0.781. A positive correlation was found between women BMI with serum orexin levels r=0.172, p=0.05 and weight of the women with orexin serum levels r=-.179, p=0.41. Conclusion: The current study concluded that mean orexin-A levels was significantly associated with BMI. But no statistical significant association between women age and mean serum orexin level has been reported. Keywords: Body mass index, Orexin-A levels, Reproductive age group women.